ART, LAW AND SUSTAINABILITY: : ENVIRONMENTAL PRESERVATION AS CULTURAL HERITAGE IN THE ERA OF CLIMATE CRISIS (Interdisciplinary Studies Journal, 2025)
This article explores the possibilities of integrating corporate socio-environmental responsibility and artistic expressions as instruments for promoting sustainable development in Brazil. Through an interdisciplinary approach that connects law, art, and the environment, the study examines the social and ecological function of the company within the constitutional order, the normative framework of environmental governance, and legal mechanisms for cultural incentives. It demonstrates how business practices aimed at sustainability have incorporated artistic manifestations as a means of social awareness, community mobilization, and institutional image building. Case studies and legal proposals are analyzed to institutionalize this intersection as a permanent development strategy. The article concludes that art can play a central role in building a corporate legal culture committed to sustainability, cultural rights, and social transformation, thus becoming an essential vector in reshaping business practices in response to contemporary ecological and social demands.
Keywords: Responsibility; Development; Art; Governance; Ecology